Clients' expectations and experiences with providers of menstrual regulation: a qualitative study in Bangladesh - Ana Maria Ramirez; Tanzila Tabassum; Sofia Filippa; Anna Katz; Rezwana Chowdhury; Chiara Bercu; Sarah E. Baum (BMC, 2024)
Abstract Background Menstrual Regulation (MR) has been legal in Bangladesh since 1979 in an effort to reduce maternal mortality from unsafe abortion care. However, access to high-quality and patient-centered MR care remains a challenge. This analysis aimed to explore what clients know before going into care and the experience itself across a variety of service delivery sites where MR care is available. Methods We conducted 26 qualitative semi-structured interviews with MR clients who were recruited from three different service delivery sites in Dhaka, Bangladesh from January to March 2019. Interviews explored client expectations and beliefs about MR care, the experience of the care they received, and their perception of the quality of that care. We conducted a thematic content analysis using a priori and emergent codes. Results Clients overall lacked knowledge about MR care and held fears about the damage to their bodies after receiving care. Despite their fears, roughly half the clients held positive expectations about the care they would receive. Call center clients felt the most prepared by their provider about what to expect during their MR care. During counseling sessions, providers at in-facility locations reinforced the perception of risk of future fertility as a result of MR and commonly questioned clients on their need for MR services. Some even attempted to dissuade nulliparous women from getting the care. Clients received this type of questioning throughout their time at the facilities, not just from their medical providers. The majority of clients perceived their care as good and rationalized these comments from their providers as coming from a caring place. However, a handful of clients did report bad care and negative feelings about their interactions with providers and other clinical staff. Conclusion Providers and clinical staff can play a key role in shaping the experience of clients accessing MR care. Training on accurate knowledge about the safety and effectiveness of MR, and the importance of client communication could help improve client knowledge and person-centered quality of MR care.